Clean and Healthy Living Behavior among Students of Islamic Boarding Schools - Yenny Rachmawati; Citra Ariani; Sulpiana Sulpiana; Desdiani Desdiani (CV. Global Health Science Group, 2026)
Islamic boarding schools (pesantren), community-based institutions providing intensive Islamic and general education, play an essential role in shaping students’ daily health behaviors. However, limited health knowledge and suboptimal sanitation conditions continue to pose challenges to the promotion of clean and healthy living behavior (Perilaku Hidup Bersih dan Sehat, PHBS) in this environment. This Cross-sectional study assessed the PHBS knowledge, attitudes, and practices in an Islamic boarding school in Depok, West Java, Indonesia. Data were collected using a structured knowledge, daily practices, facilities and infrastructure, institutional support, sanitation, and environmental health risks. Convenience sampling was used, validity was established through theory-driven content development and face validity. Descriptive and inferential statistics were used to analyze responses and examine gender differences. Basic hygiene practices such as handwashing and bathing showed high compliance (>80%), but preventive behaviors, including vector control and environmental sanitation, remained low (<30%). Knowledge of key health issues, including HIV/AIDS transmission, was limited. Significant gender differences were found in certain practices and reported health complaints. Inadequate facilities, weak institutional support, and high exposure to environmental health risks were identified as persistent challenges. Findings highlight the need for a comprehensive, multi-level approach combining infrastructure improvements, targeted health education, and strengthened institutional roles to promote sustainable PHBS among pesantren students.